Actualization Of Human Rights Values Through Bureaucratic Reform Towards Justice Bureaucratic Governance - Edy, Nurul (Journal of Local Government Issues, 2019)
Before entering the reform era, bureaucratic governance in Indonesia was characterized by the practice of collusion and nepotism in which the bureaucracy could not carry out its duties and obligations professionally and they could not achieve their careers fairly and sustainably. Therefore, the aim of bureaucratic reform is to realize fair bureaucratic governance in which bureaucratic apparatus can carry out their duties and obligations professionally and the bureaucracy can reach career paths as a state apparatus fairly and professionally. So far, bureaucratic reform has not yet reached its objectives, where bureaucratic governance, especially in the context of the promotion of the position of state civil apparatus (ASN), is still colored by the practice of collusion and nepotism caused by high political intervention in ASN promotion. Regional autonomy and regional head elections are wrong which causes bureaucratic reform to not work effectively. The regional head who is the result of the regional election places ASN in the strategic position of regional apparatus according to their political interests, not based on the potential possessed by the ASN. For this reason, the design of bureaucratic reforms needs to be reorganized so that the gap of political intervention in bureaucratic governance can be minimized in order to realize a professional bureaucracy. Keywords: Bureaucracy, Bureaucratic Reform, Human Rights